2018
DOI: 10.24929/lensa.v7i1.19
|View full text |Cite
|
Sign up to set email alerts
|

Studi Kelayakan Pengelola Laboratorium Ipa SMPN 4 Sumenep Berdasarkan Permendagri 26/2008

Abstract: Penelitian ini bertujuan untuk mendeskripsikan kinerja pengelola laboratorium IPA SMPN 4 Sumenep Tahun Pelajaran 2014/2015. Fokus penelitian diarahkan pada pengelola laboratorium IPA berdasarkan kompetensi pengelola dalam Permendiknas 26/2008. Metode penelitian yang digunakan adalah metode deskriptif kualitatif. Data penelitian dikumpulkan melalui wawancara, dokumentasi, dan observasi. Seluruh data yang terkumpul dianalisis menggunakan metode interaktif Miles dan Huberman kemudian diperiksa kebenarannya menggu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The significance value was <0.05, which means that the learning achievement of the skill was rejected and it can be concluded that there were significant differences in student achievement in the skill domain. This difference can be seen from the results of the average value in the domain of skills which showed that the value in the experimental class was higher than the control class according to the research conducted by Meita [14] which showed that the class given treatment using REACT model had a skill value in the process higher than the class that was not given treatment with the model. Differences that occur in the results of skill learning achievement can be caused by student's learning achievement, especially in the different skill domain with the difference of curiosity of the experimental and exploration activities.…”
Section: Transferringmentioning
confidence: 96%
“…The significance value was <0.05, which means that the learning achievement of the skill was rejected and it can be concluded that there were significant differences in student achievement in the skill domain. This difference can be seen from the results of the average value in the domain of skills which showed that the value in the experimental class was higher than the control class according to the research conducted by Meita [14] which showed that the class given treatment using REACT model had a skill value in the process higher than the class that was not given treatment with the model. Differences that occur in the results of skill learning achievement can be caused by student's learning achievement, especially in the different skill domain with the difference of curiosity of the experimental and exploration activities.…”
Section: Transferringmentioning
confidence: 96%
“…So learning facilities are very important for every educational institution for the continuity of the teaching and learning process so that students can learn in conditions that are comfortable and interesting to pay attention to. According to Meita (2017) [17] , facilities are anything that directly supports the smooth learning process, for example learning media, learning tools, school equipment, and so on.…”
Section: Learning Facilitiesmentioning
confidence: 99%
“…Namun berdasarkan hasil penelitian (Meita, 2017), masih banyak beberapa hal mekanis dan teknis yang seharusnya dilakukan oleh pengelola laboratorium IPA namun tidak dilakukan. Kompetensi manajerial dan profesional Kepala laboratorium IPA hampir keseluruhan belum terlaksana, sedangkan guru-guru IPA yang terlibat dalam pengelolaan laboratorium IPA sebagai laboran/teknisi yakni sebagian terlaksana dan sebagian tidak terlaksana.…”
Section: Pendahuluanunclassified